LIPASE FROM Rhizopus oryzae IMMOBILIZED ON CORN COB POWDER: A NEW APPROACH FOR DIETETIC TRIGLYCERIDE SYNTHESIS IN A FIXED BED REACTOR - Pacheco, Bruna Jeanne Soares; Andrade, Grazielle Santos Silva; Paula, Ariela Veloso de [UNESP] (Soc Brasileira Quimica, 2024)
This work explores the possibility of using corn cob powder as a carrier for immobilization by physical adsorption of lipase from Rhizopus oryzae used in acidolysis reaction of grape seed oil with capric acid (C10) to synthesize dietary triglycerides (TAGs) formed from medium-long-medium chain (MLM) fatty acids in a fixed bed reactor. First, enzymatic loading was investigated to improve hydrolytic activity and the immobilized biocatalyst was characterized in terms of biochemical parameters and thermal stability. An enzyme load of 30 mg mL-1 was quite adequate, as about 90% of the immobilization yield was achieved. The central composite rotatable design (CCRD) experimental design revealed that, for the immobilized enzyme, the optimal hydrolytic activity was obtained at pH 7.75 and 41 degrees C. Stirred tank reactions were optimized in CCRD statistical analysis revealing the most desirable conditions for molar ratio of 1:9.36 (oil:acid), 45 degrees C and 15% biocatalyst, obtaining a maximum ID value of 86.93 +/- 2.25%. In a fixed bed reactor, the synthesis showed an average ID of 51.13 +/- 0.77%, demonstrating the potential of this configuration. It is concluded that corn cob powder as an immobilization carrier is a promising alternative for the enzymatic synthesis of MLM triacylglycerols.
Keywords: dietary triglycerides; grape seed oil; immobilization; corn cob powder; fixed bed reactor